Inexistent Night (with Yasunari Kawabata). Issue 2 (4th May 2019) - Bahbak Mohaghegh, Jason
ABSTRACT: This piece theorizes the myriad strange possibilities of "the inexistent night" – that is, a minor temporal-existential break in the after-dark that nevertheless enables both disastrous and euphoric transformations to take hold. To illustrate this subtle turn, the focus rests upon a close analysis of a text by the twentieth-century, avant-garde, Japanese writer Yasunari Kawabata titled House of the Sleeping Beauties . This is a minimalist tale of enigmatic encounters in which characters embody different cyclical moods relating night to anonymity, solitude, and impermanence. In the final stride, an entire conceptual edifice of the inexistent unfolds – amid radical disorientations of identity, desire, movement, and sensation – combining the architectonics of ghostliness with the atmospherics of shadow to suggest a more cryptic world beyond all existential centers.